2009
DOI: 10.1029/2008je003242
|View full text |Cite
|
Sign up to set email alerts
|

A new model to simulate the Martian mesoscale and microscale atmospheric circulation: Validation and first results

Abstract: [1] The Laboratoire de Météorologie Dynamique (LMD) Mesoscale Model is a new versatile simulator of the Martian atmosphere and environment at horizontal scales ranging from hundreds of kilometers to tens of meters. The model combines the National Centers for Environmental Prediction(NCEP)-National Center for Atmospheric Research (NCAR) fully compressible nonhydrostatic Advanced Research Weather Research and Forecasting (ARW-WRF) dynamical core, adapted to Mars, with the LMD-general circulation model (GCM) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
127
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 134 publications
(139 citation statements)
references
References 96 publications
(178 reference statements)
11
127
0
1
Order By: Relevance
“…The last phenomenon was the focus of the Toigo et al (2003) LES study which showed similarities between the modelled vortices and the observed Martian dust devils. These preliminary results were recently confirmed by other studies (Richardson et al, 2007;Sorbjan, 2007;Spiga and Forget, 2009). LESs were also used to investigate atmospheric hazards during the entry, descent and landing (EDL) of the Mars Exploration Rovers (MER) (Rafkin and Michaels, 2003;Toigo and Richardson, 2003) and the Phoenix lander (Michaels and Rafkin, 2008;Tyler et al, 2008).…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…The last phenomenon was the focus of the Toigo et al (2003) LES study which showed similarities between the modelled vortices and the observed Martian dust devils. These preliminary results were recently confirmed by other studies (Richardson et al, 2007;Sorbjan, 2007;Spiga and Forget, 2009). LESs were also used to investigate atmospheric hazards during the entry, descent and landing (EDL) of the Mars Exploration Rovers (MER) (Rafkin and Michaels, 2003;Toigo and Richardson, 2003) and the Phoenix lander (Michaels and Rafkin, 2008;Tyler et al, 2008).…”
Section: Introductionsupporting
confidence: 81%
“…For instance, Michaels and Rafkin (2004) found that the horizontal structures of updraughts simulated in LES and convective clouds observed by MOC were similar. Spiga and Forget (2009) noticed encouraging agreement between LES results in Gusev Crater and MER miniTES temperature profiles up to 2 km above the surface (Smith et al, 2006).…”
Section: Introductionsupporting
confidence: 63%
“…A pressure and wind field has been generated around the landing site thanks to a LES simulation as described in Spiga and Forget (2009). The resulting pressure noise tilt (vertical and horizontal) is estimated at two wind speeds by Sorrels method (see Fig.…”
Section: B8 Pressure Tilt Assumptionsmentioning
confidence: 99%
“…In order to focus on the seismic bandwidth, we are interested in simulations of the pressure variations between 1 s and 100 s. This level of resolution of pressure field simulations is reached only by the Large Eddy Simulations (LES) that can resolve the turbulence-related phenomena at the interface between the Martian surface and the atmosphere, plus theoretical considerations for periods below 10 seconds. High resolution LES, as described in Spiga and Forget (2009) can use grids smaller than 50 m of resolution and can therefore simulate convective motions of the atmosphere as well as the large vortices and turbulent structures such as dust devils, which are expected to be the main source of turbulence related tilt noise in our bandwidth.…”
Section: Pressure Field Assumptionsmentioning
confidence: 99%
“…pressure drops of a few Pascals, sizes from a few tens to hundreds of meters, vertical extension of about a kilometer, and durations from a few tens to at most a few thousands of seconds (Rafkin et al 2001;Toigo and Richardson 2003;Michaels and Rafkin 2004;Spiga and Forget 2009;Gheynani and Taylor 2011). Those parameters are generally all larger for martian dust devils than for their terrestrial counterparts, which is consistent with the generally larger dust flux supposedly originating from Mars's dust devils compared to Earth's.…”
mentioning
confidence: 99%